The Stand Of Electronic Evidence In Cyber Crime Law Enforcement In Indonesia - Dewic Sri Ratnaning Dhumillah (Eduvest - Journal of Universal Studies, 2024)
Crime in the cyber world certainly has a significant impact. People think that Indonesia has a Criminal Code that cannot cover crimes in cyberspace, which is a new crime. This is what makes the government have to issue regulations regarding cyber crime or cyber crime. With regard to enforcing cybercrime law, of course, a regulation is needed in positive law. It also regulates the punishment and how the evidence for cyber crimes and the position of electronic evidence are. This research method uses the normative method. The existence of electronic evidence in proving cybercrime has been alluded to in Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions. In Article 5 of Law Number 11 of 2008, it explicitly mandates that "Electronic Information and/or Electronic Documents and/or their printouts are valid legal evidence". This can be interpreted that electronic documents are considered legally valid according to positive law in Indonesia. However, in the amendment to the elucidation of Article 5 paragraph (1) regulated in Law Number 19 of 2016, it is explained that the existence of Electronic Information and/or Electronic Documents is binding and recognized as valid evidence to provide legal certainty for the Implementation of Electronic Systems and Transactions Electronic, especially in proving and matters relating to legal actions carried out through Electronic Systems.